The Influence of the Mind Mapping Learning Model on Narrative Text Comprehension in Elementary School Students - Latifah, Husnul; Pebriana, Putri Hana; Anry, Aura Afrillia; Ashilah, Jihan; Fadillah, Nur; Aprilia, Putri Rudini; Angelica, Niken; Junita, Yola (The Future of Education Journal, 2025)
This study aims to evaluate the effectiveness of the mind mapping learning model in improving elementary school students' narrative writing skills. By analyzing various published journals, it was found that the implementation of this model shows significant results in addressing the challenges faced by students in writing. Although there are some limitations in these studies, the analysis indicates that the mind mapping model can assist students in organizing ideas and composing texts more effectively. This article provides a comprehensive overview of the strengths and weaknesses of using the mind mapping learning model in the context of Indonesian language education.